2009
DOI: 10.1021/ie9011672
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cellulose Nanofibers from Two Commercial Hardwood and Softwood Pulps

Abstract: The aim of this work was to study the mechanical fibrillation process for the preparation of cellulose nanofibers from two commercial hard-and softwood cellulose pulps. The process consisted of initial refining and subsequent high-pressure homogenization. The progress in fibrillation was studied using different microscopy techniques, mechanical testing, and fiber density measurements of cellulose films prepared after different processing stages. The mechanical properties of cellulose films showed an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(171 citation statements)
references
References 36 publications
4
160
2
5
Order By: Relevance
“…In the HCNF and PCNF paper sheets, the tensile strength and elastic modulus in the softwoods was higher than those in the hardwoods. Stelte and Sanadi (2009) and Spence et al (2010) also reported that the tensile properties of nanopapers prepared from softwood pulp were higher than those prepared from hardwood nanopaper. These results are assumed to be due to the greater length and high aspect ratio of the softwood fiber.…”
Section: Tensile Properties Of Nanopapermentioning
confidence: 95%
“…In the HCNF and PCNF paper sheets, the tensile strength and elastic modulus in the softwoods was higher than those in the hardwoods. Stelte and Sanadi (2009) and Spence et al (2010) also reported that the tensile properties of nanopapers prepared from softwood pulp were higher than those prepared from hardwood nanopaper. These results are assumed to be due to the greater length and high aspect ratio of the softwood fiber.…”
Section: Tensile Properties Of Nanopapermentioning
confidence: 95%
“…The process in fibrillation was studied using different microscopy techniques, mechanical testing, and fiber density measurements of cellulose films prepared after different processing stages. An increase in processing steps obviously increases the energy required for fibrillation [63]. For the island-in-sea method, fibers of diameter less than one micrometer can be made by the conjugated spinning method, in which two polymer components are extruded together from a spinning die.…”
Section: Template Methodsmentioning
confidence: 99%
“…Facial tissues are made from wood pulp, which is obtained from both hardwood and softwood. Hardwoods are, in general, more complex and heterogeneous in structure than softwoods, and they have shorter fiber cells than softwoods [1]. In addition, softwood fibers are known to be stronger than hardwood fibers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hardwoods are, in general, more complex and heterogeneous in structure than softwoods, and they have shorter fiber cells than softwoods [1]. In addition, softwood fibers are known to be stronger than hardwood fibers [1]. Facial tissues produced by mixing these two types of wood pulp at certain rates allow for desired properties, such as softness and strength, to be obtained.…”
Section: Introductionmentioning
confidence: 99%